2011
DOI: 10.1093/ndt/gfr345
|View full text |Cite
|
Sign up to set email alerts
|

Renal perfusion evaluation with contrast-enhanced ultrasonography

Abstract: This study demonstrates that CEUS is able to detect changes in human renal cortical microcirculation as induced by AngII infusion and/or captopril administration. The changes in perfusion indices parallel those in ERPF as obtained by PAH clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 26 publications
6
77
0
2
Order By: Relevance
“…45 healthy volunteers were included as control group. All statistical analyses were performed with SPSS® v. 15.0 software package (SPSS, Chicago, IL). A difference was considered statistically significant with p , 0.05.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…45 healthy volunteers were included as control group. All statistical analyses were performed with SPSS® v. 15.0 software package (SPSS, Chicago, IL). A difference was considered statistically significant with p , 0.05.…”
mentioning
confidence: 99%
“…12 CE ultrasound has been recently used as a new imaging technique for quantifying tissue perfusion changes in the liver, 13 heart 14 and kidney. 15 The large blood supply of the kidney was a good base for contrast studies, as .90% of kidney blood flow supplied the renal cortex by the renal arterioles and capillaries. 16 Since CE ultrasound microbubbles remain strictly inside the vessels, they can be viewed as bloodpool markers enabling functional imaging of the kidney.…”
mentioning
confidence: 99%
“…CEUS has also been used to evaluate renal microvascular perfusion following the administration of vasoactive drugs. CEUS ascertained parameters decreased after the use of angiotensin II (Ang II), and increased after captopril (Ang II inhibitor) administration [32] . Noradrenaline- [33] and dopamineinduced [34] changes in renal perfusion were also correctly validated by CEUS.…”
Section: Renal Microvascular Perfusion Evaluation In Humans Using Ceusmentioning
confidence: 99%
“…Schwenger [72] and Benozzi [73] et al demonstrated that contrast-enhanced ultrasound was able to distinguish acute rejection from acute tubular necrosis. Another study, in healthy volunteers demonstrated that contrast-enhanced ultrasound was able to detect a 20 % decrease in renal blood fl ow as induced by an angiotensin II infusion [74]. Above all, contrast-enhanced ultrasound can provide real time visualization of the renal microcirculation.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%